Bullying and being bullied: prevalence and psychosocial outcomes among school going adolescents of Rohtak - ., Shiba; Rajput, Meena; Goutam, Ankit; Rajawat, Gaurav (International Journal Of Community Medicine And Public Health, 2018)
Background: Bullying is a problem which is commonly faced by so many school going children and adolescents usually in the form of nasty teasing, name-calling, threatening, physically hurting, exclusion from group, spreading false rumors etc. A victim of bullying is at increased risk of behavioural and emotional problems, depression, psychotic symptoms including anxiety, insecurity and poor school performance. The objectives of the study were to measure the prevalence of bullying behaviours among adolescents and to determine the effects of bullying and being bullied on psychosocial adjustment. Methods: Cross-sectional study was carried out from August, 2016 to February, 2017 among school going adolescents 11-18 yrs of age. A total of 300 students were chosen using multi stage sampling from ten schools of five community development blocks of Rohtak. Results: Out of 300 participants 176 (58.7%) were male, 124 (41.3%) were female. 21.6% (65) students bullied other students, 19% (57) were being bullied. More boys reported bullying others and being victims of bullying. Conclusions: The effects of being bullied are direct, pleiotropic and long- lasting with the worst effects for those who are both victims and bullies.